Peran Akun Instagram @republikuntidar_ dalam Membentuk Persepsi dan Antusiasme Mahasiswa FISIPOL UNTIDAR 2024 terhadap Organisasi Mahasiswa - medianti, lintang laila (Saraq Opat: Jurnal Administrasi Publik, 2025)
This study aims to describe the level of exposure, perception, and enthusiasm of FISIPOL UNTIDAR 2024 students towards the independent Instagram account @republikuntidar_, which functions as an advocacy platform. A descriptive quantitative method was used with a sample of 88 selected respondents through stratified random sampling. The instrument used was a closed questionnaire that had been tested for validity and reliability. Descriptive analysis showed that 92% of respondents knew the account and 85% followed it, with a mean exposure of 4.1 (median 4.0). Student perceptions were positive (mean 3.9; median 4.0), where 70% agreed that this account clarified advocacy issues, 68% felt the benefits of the information, and 66% assessed the credibility of the message. Enthusiasm was reflected in the mean 3.7 (median 3.8): 69% were interested in participating in the advocacy campaign, but only 50% were ready to allocate time, indicating implementation barriers. The limitations of the descriptive design and limited sample size encourage recommendations for further research using inferential analysis (regression), population expansion, and mixed approaches (quantitative-qualitative) to explore motivations and barriers to advocacy participation. Moderator variables such as audience trust and media literacy need to be explored, and evaluation of content formats (video, infographics, stories) can improve the effectiveness of digital advocacy strategies.